Free Radicals in Diseases and Potential Role of Phytoconstituents-A Cause with Emerging Importance - Mukherjee, Sukhes; B. Gogoi, J. (Current Chemical Biology, 2011)
Free radicals and oxidants play a dual role as both toxic and beneficial compounds, which in low/moderate concentrations are involved in normal physiological functions but excess production of free radicals or decrease in antioxidant level leads to oxidant stress. Free radicals are produced either from normal cell metabolisms in situ or from different external sources (pollution, cigarette smoke, radiation, medication etc). When an overload of free radicals cannot gradually be destroyed, their accumulation in the body is a harmful process that can mediate damage to cellular structures, including lipids, proteins, RNA and DNA leading to a number of diseases. ROS (reactive oxygen species) and RNS (reactive nitrogen species) in excess can damage biological processes, and this situation has been observed in various acute and chronic diseases such as cancer, autoimmune disorders, aging, cataract, cardiovascular and neurodegenerative diseases. This review deals in depth with the role of free radical generation, the mechanisms of formation and catabolism, and the role in various diseases and the function of different phytoconstituents as a defensive factor in the treatment of diseases caused by free radicals, as in the new era they are conferring less side effects and are compatible to body physiology.
Keywords: Crohn' s disease